Association between tooth loss and body mass index among older adults in Kuala Pilah, Negeri Sembilan - Tanti Irawati Rosli,; Chan, Yoke Mun; Rahimah Abdul Kadir,; Tengku Aizan Abdul Hamid, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Loss of teeth can affect masticatory efficiency in older adults. This may result in avoidance or modifications in food choices and lead to lower intake of important nutrients among older individuals. The aim of this study was to determine the association between tooth loss and body mass index, BMI, among older adults in Kuala Pilah, Negeri Sembilan. A cross-sectional study was carried out on 428 older adults aged 50 years and above from selected villages in district of Kuala Pilah. Respondents were interviewed to collect information on their demographic characteristics. Number of tooth loss was determined through oral assessment, followed by anthropometric assessment to calculate the BMI of respondents. Findings showed that majority of the respondents were overweight and obese, 40.4% and 19.9% respectively, while only a small proportion was underweight, 3.9%. The proportion of edentulism (total tooth loss) was 18.3% and majority of the older adults had lost more than 12 teeth (77.1%) and less than 4 pairs of occluding posterior teeth (86.0%). Total and partial tooth loss was found to be not significantly associated with BMI. In relation to the arrangement of teeth, older adults with reduced number of posterior occluding pairs of teeth were more likely to experience unsatisfactory BMI (OR = 3.61, 95% CI: 1.48, 8.76). This may suggest that functional arrangement of the tooth in the oral cavity is more important than the number of tooth loss alone. Thus, maintaining an optimum number of teeth for chewing is essential for maintenance of ideal BMI.